2018
DOI: 10.1136/bmj.k2575
|View full text |Cite
|
Sign up to set email alerts
|

Predicted lean body mass, fat mass, and all cause and cause specific mortality in men: prospective US cohort study

Abstract: ObjectiveTo investigate the association of predicted lean body mass, fat mass, and body mass index (BMI) with all cause and cause specific mortality in men.DesignProspective cohort study.SettingHealth professionals in the United StatesParticipants38 006 men (aged 40-75 years) from the Health Professionals Follow-up Study, followed up for death (1987-2012).Main outcome measuresAll cause and cause specific mortality.ResultsUsing validated anthropometric prediction equations previously developed from the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
322
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 327 publications
(334 citation statements)
references
References 45 publications
9
322
1
2
Order By: Relevance
“…This explains why we observed a positive association between predicted lean body mass and CRC risk. In contrast, we recently reported that an inverse relationship between BMI and mortality associated with respiratory disease was largely due to lean body mass . Our current findings suggest that BMI can be a good measure of obesity at least for estimating the risk of CRC regardless of age.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This explains why we observed a positive association between predicted lean body mass and CRC risk. In contrast, we recently reported that an inverse relationship between BMI and mortality associated with respiratory disease was largely due to lean body mass . Our current findings suggest that BMI can be a good measure of obesity at least for estimating the risk of CRC regardless of age.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, we recently reported that an inverse relationship between BMI and mortality associated with respiratory disease was largely due to lean body mass. 22 Our current findings suggest that BMI can be a good measure of obesity at least for estimating the risk of CRC regardless of age. Observed heterogenous susceptibilities of obesity with the risk of CRC were consistent with a large body of previous literature.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This gives room for thought whether it is a true shortage of muscle mass, or a relative excess of fat mass, or both that is associated with NAFLD. Interestingly, a recent population‐based study found that the two body components, lean body mass and fat mass, both explained the relation between BMI and mortality . To the best of our knowledge, there are no studies that have examined the role of both components, independent of each other, in relation to NAFLD.…”
Section: Introductionmentioning
confidence: 99%